Pengembangan Paket Wisata Heritage di Kota Bandung Jawa Barat - Hadi Mulyana; Ghifari Abdul Razaq (Manajemen dan Pariwisata, 2026)
Until this time, there are many kinds of tourism activities, one of which is heritage tourism. Many areas and destinations offer the charm of heritage tourism, for example Kota Bandung. Kota Bandung holds a lot of heritage and past history charm that can attract many of tourists. The purpose of this research is to determine the condition of heritage tourism in Bandung, determine heritage tourism packages in Bandung and find out how to develop heritage tourism packages in Bandung. While the research method in this research is descriptive research with qualitative approach. Data collection techniques used are observation, interviews, literature study and documentation with purposive sampling technique. The results from the research show that heritage tourism in Bandung from the aspects of attractions, facilities, time and tourists unfortunately in a less organized conditions. To solve that, the development should follow the 5 principles of heritage tourism packages development according to the heritage tourism handbook so that the heritage tourism packages in Kota Bandung can be developed better optimally.